2003
DOI: 10.2337/diabetes.52.5.1098
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Euglycemia and Normal Acute Insulin Response to Glucose in Obese Subjects With Type 2 Diabetes Following Bariatric Surgery

Abstract: Insulin resistance and loss of glucose-stimulated acute insulin response (AIR) are the two major and earliest defects in the course of type 2 diabetes. We investigated whether weight loss after bariatric surgery in patients with morbid obesity and type 2 diabetes could restore euglycemia and normal AIR to an intravenous glucose tolerance test (IVGTT). We studied 25 morbidly obese patients-12 with type 2 diabetes, 5 with impaired glucose tolerance, and 8 with normal glucose tolerance (NGT)-before and after a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
134
2
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(160 citation statements)
references
References 43 publications
10
134
2
9
Order By: Relevance
“…Glucose tolerance and insulin sensitivity were significantly heightened post-surgery, even in patients who were NGT at baseline. Previous studies [4][5][6][7] have shown that bariatric surgery is extremely effective in improving glucose tolerance, insulin sensitivity and, to some extent, insulin secretion (as inferred from homeostasis model assessment estimates or the acute insulin response to i.v. glucose).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose tolerance and insulin sensitivity were significantly heightened post-surgery, even in patients who were NGT at baseline. Previous studies [4][5][6][7] have shown that bariatric surgery is extremely effective in improving glucose tolerance, insulin sensitivity and, to some extent, insulin secretion (as inferred from homeostasis model assessment estimates or the acute insulin response to i.v. glucose).…”
Section: Discussionmentioning
confidence: 99%
“…In morbidly obese patients undergoing bariatric surgery, one factor contributing to the restoration of normal glucose tolerance is the surgery-induced increase in insulin sensitivity [4][5][6][7]. Although some data are available [5,[7][8][9], the role of beta cell function, its relationship with insulin sensitivity, and the contribution of either factor to the improvement in glucose tolerance are not clearly established.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…26,36 Improvements in insulin resistance and b-cell function have been documented following surgical weight loss. 36,[106][107][108][109] Interestingly, although significant improvements in carbohydrate metabolism occur after surgical weight loss in adults, studies also demonstrate that in response to a glucose challenge there is only incomplete normalization of parameters of insulin secretion and insulin resistance. [106][107][108][109][110][111] Adolescents undergoing bariatric surgery also demonstrate significant fasting hyperinsulinemia and insulin resistance as estimated by homeostasis model assessment (HOMA-IR) was abnormal in 64% of patients preoperatively.…”
Section: Endocrine Changesmentioning
confidence: 99%
“…Food intake restriction is achieved by reducing the size of stomach (gastric band, sleeve gastrectomy) and/ or by resecting the small intestines (biliopancreatic diversion, gastric bypass). Bariatric surgery can achieve full remission of the T2DM syndrome [31,32] (Figure 17). …”
Section: Metformin and Other Drugs Which Influence Energy Exchange (Nmentioning
confidence: 99%